Empagliflozin after myocardial infarction with or without diabetes and chronic kidney disease: insights from EMPACT-MI - Fioretti, Francesco; Butler, Javed; Udell, Jacob A.; Schuyler Jones, W.; Petrie, Mark C.; Harrington, Josephine; Mattheus, Michaela; Bauersachs, Johann; Bayes-Genis, Antoni; Goodman, Shaun G.; Gasior, Tomasz; Januzzi, James L.; et al. (ESC heart failure, 2025)
Background In the EMPACT-MI trial, empagliflozin did not reduce the primary endpoint of all-cause mortality or hospitalization for heart failure (HHF) following acute myocardial infarction (AMI) but was associated with a risk reduction for HF events. Objectives This study aimed to evaluate whether the effect of empagliflozin on HF events is consistent in patients with and without type 2 diabetes and/or chronic kidney disease enrolled in the EMPACT-MI trial. Methods Post hoc analysis assessing the effect of empagliflozin on the primary endpoint and on HF events in AMI patients with and without an established recommendation for a sodium-glucose cotransporter-2 inhibitor (SGLT2i) (type 2 diabetes or chronic kidney disease). Results Of 6522 participants, 3489 (53%) did not have type 2 diabetes and/or chronic kidney disease. Those without these conditions were younger and with fewer comorbidities. No differences were observed for the primary endpoint. Empagliflozin reduced time to first HHF, total HHF, time to adverse event (AE) of HF (including outpatient HF events) and total AEs of HF similarly in patients with and without type 2 diabetes or chronic kidney disease. Total HHFs were 50 and 63 [adjusted event rate 1.74 and 2.31 events per 100 patient-years; rate ratio (RR) 0.75; 95% confidence interval (CI) 0.48, 1.18] in patients without and 98 and 144 (adjusted event rate 3.91 and 6.04 events per 100 patient-years; RR 0.65; 95% CI 0.45, 0.94; P for interaction = 0.61) in those with type 2 diabetes or chronic kidney disease in the empagliflozin and placebo arms, respectively. Any AEs, serious AEs and AEs leading to permanent study drug discontinuation were similar between treatment groups in both subgroups. Conclusions Empagliflozin improved HF outcomes similarly in patients after AMI with or without type 2 diabetes or chronic kidney disease.